Implementation of Water-Saving Irrigation Technologies Agricultural Crop Productivity Guarantee - Sadullayev B.O (Zien Journals, 2022)
In the conditions of water shortage due to global climate changes in Uzbekistan, in order to obtain a high yield from agricultural crops and to provide the population with food products, it is important to use the existing water resources effectively and to widely introduce cost-effective irrigation technologies. have In our country, large-scale works on efficient and targeted use of water are being carried out. In particular, more than 5,000 kilometers of irrigation, 12,000 kilometers of collector-drainage, and 50,000 kilometers of canal networks are being cleaned every year. More than 200 kilometers of canals, 530 kilometers of channel and collector networks, more than 400 hydrotechnical structures and many other objects are being reconstructed and built
Keywords: water saving; climate; technology; film